The Hebrew Bible and philosophy of religion, Jaco Gericke : book review - Bothma, G (Journal for semitics, 2014)
In this interdisciplinary study Jaco Gericke pioneers combining the study of the philosophy of religion and the study of the Hebrew Bible. He demonstrates that certain types of descriptive varieties of philosophy of religion exist that are capable of aiding the clarification of meaning in the Hebrew Bible. In this process a theologically interesting and hermeneutically legitimate nonrealist descriptive perspective on the Hebrew Bible is given. While avenues for more objective theological thinking is opened up, the study enables biblical scholars of different persuasions to access levels of meaning that lie beyond the scope of linguistic, literary, historical and social-scientific perspectives on the text.